Trace elements in market vegetables of Kuantan, Pahang: A preliminary estimate of dietary exposure - Nur Wirdah, Sulong; Nazikussabah, Zaharudin; Tay, Joo Hui (Penerbit Universiti Malaysia Pahang, 2023)
A pilot study was conducted to investigate the concentrations of ten trace elements: Copper (Cu), iodine (I), manganese (Mn), molybdenum (Mo), nickel (Ni), selenium (Se), zinc (Zn), arsenic (As), cadmium (Cd) and lead (Pb) in nine ready-to-eat market vegetables collected from Kuantan, Pahang. Samples of vegetables were obtained from a local market, acid-digested using open digestion method and then analysed for elements using Inductively Coupled Plasma - Mass Spectrometry (ICP-MS). The mean concentration of essential elements decreased in the following order: Mn>Zn>Mo>Cu>I>Ni>Se, with individual concentrations ranging from below detection limit (bdl) to 207 mg/kg dw. Cadmium, a non-essential element, was detected in 8 samples at a mean concentration of 0.06 mg/kg dw, while Pb and As were not detected (bdl) in all samples. The estimated daily dietary intake (EDI) as well as the potential health risk associated with vegetable consumption were calculated. Hazard quotient (HQ) values less than one were obtained for both children and adults, indicating that consumption of these vegetables poses low risk to health.